1998
DOI: 10.1046/j.1365-2486.1998.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics and genotypic variation in tropical, field‐grown paddy rice (Oryza sativa L.) in response to increasing carbon dioxide and temperature

Abstract: While previous studies have examined the growth and yield response of rice to continued increases in CO2 concentration and potential increases in air temperature, little work has focused on the long‐term response of tropical paddy rice (i.e. the bulk of world rice production) in situ, or genotypic differences among cultivars in response to increasing CO2 and/or temperature. At the International Rice Research Institute, rice (cv IR72) was grown from germination until maturity for 4 field seasons, the 1994 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 27 publications
7
71
1
Order By: Relevance
“…Kimball et al, 2002), since [CO 2 ] is a growth-limiting resource for C 3 plants. There is a large genotypic variation in the yield response to eCO 2 , both among cultivars and between species, with responses ranging from -15% to +20% per 100 mmol mol -1 CO 2 increase from the current level for rice (Ziska et al, 1996;Moya et al, 1998;Baker, 2004;Shimono et al, 2009;Hasegawa et al, 2013), -6% to +35% for wheat (Manderscheid and Weigel, 1997;Ziska et al, 2004;Ziska, 2008;Tausz-Posch et al, 2015), -5% to +55% for soybean (Ziska and Bunce, 2000;Ziska et al, 2001;Bishop et al, 2015;Bunce, 2015), and -6% to +21% for field bean (Phaseolus vulgaris; Bunce, 2008). These large differences in eCO 2 responsiveness within crop species suggest that active selection and breeding for genotypes that respond strongly to gradual but steadily increasing [CO 2 ] may ensure sustained productivity and improve food security in a future eCO 2 world (Ainsworth et al, 2008;Ziska et al, 2012;Tausz et al, 2013).…”
mentioning
confidence: 99%
“…Kimball et al, 2002), since [CO 2 ] is a growth-limiting resource for C 3 plants. There is a large genotypic variation in the yield response to eCO 2 , both among cultivars and between species, with responses ranging from -15% to +20% per 100 mmol mol -1 CO 2 increase from the current level for rice (Ziska et al, 1996;Moya et al, 1998;Baker, 2004;Shimono et al, 2009;Hasegawa et al, 2013), -6% to +35% for wheat (Manderscheid and Weigel, 1997;Ziska et al, 2004;Ziska, 2008;Tausz-Posch et al, 2015), -5% to +55% for soybean (Ziska and Bunce, 2000;Ziska et al, 2001;Bishop et al, 2015;Bunce, 2015), and -6% to +21% for field bean (Phaseolus vulgaris; Bunce, 2008). These large differences in eCO 2 responsiveness within crop species suggest that active selection and breeding for genotypes that respond strongly to gradual but steadily increasing [CO 2 ] may ensure sustained productivity and improve food security in a future eCO 2 world (Ainsworth et al, 2008;Ziska et al, 2012;Tausz et al, 2013).…”
mentioning
confidence: 99%
“…Additional studies have confirmed that there is significant intraspecific variation in the yield response to elevated CO 2 among cowpea (Vigna unguiculata, L., Walp.) [7], common bean (Phaseolus vulgaris L.) [8], rice (Oryza sativa L.) [9,10], wheat (Triticum aestivum L.) [11] and soybean (Glycine max L. Merr.)…”
mentioning
confidence: 99%
“…) show little or no photosynthetic response to elevated CO 2 , because they are CO 2 saturated and not competitively inhibited by O 2 . The increase in CO 2 is expected to cause global warming by absorbing the long wave heat radiation from the earth surface and altering the precipitation (Moya et al 1998) -i.e. climatic effect.…”
mentioning
confidence: 99%